Internal Influences on Consumer Behavior of Burgarooh Restaurant: A Case in the Fast Food Industry of Oman - Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2021)
Internal Influences on Consumer Behavior of Burgarooh Restaurant: A Case in the Fast Food Industry of Oman Nasser Juma Al Harthi MBA, Middle East College Email: PG19S2039@mec.edu.com Dr. Maria Teresa Matriano Assistant Professor, Department of Post-Graduate Studies, Middle East College, Oman Email: maria@mec.edu.om Abstract Purpose:- The Sultanate of Oman is one of the countries where the restaurant and fast food sectors are active. The study aims to analyze the factors affecting customers' choice of fast food. This research measures both personal and psychological elements on buying fast food in the Sultanate of Oman. This project is concerned with the internal influences of personal factors and factors that interact with the individual consumer. Design / methodology / approach:- The research has attempted to sample 486 customers of the restaurant from its various branches and used survey questionnaire and online interviews for data collection. Interviews were facilitated with group of customers in the restaurant branches in the Governorate of Muscat. Findings:- The study concluded that the most critical factor in choosing a burger for the consumer is that it is a means for family and friends' participation by 44%. In comparison, 43% of the participants considered that the preparation speed is one of the main factors in choosing burger meals. The study also indicated that the product's price is one of the least influencing factors for selecting the product. Moreover, the study has also concluded that fast food consumption is based on community participation and accessibility rather than direct personal choices. Research limitation / Implications:- The study indicated that product's price is the least influencing factors for selecting the product and concluded that fast food consumption is based on community participation and accessibility rather than direct personal choices. Originality / value:- There are no previous studies conducted on internal influences on consumer behavior. The study places psychological factors, which represent convictions and beliefs, at the forefront of the factors affecting the consumer's buying decision.